The Sudeten Crisis in 1938 and the Problem of the Red Army’s Passage through Poland - Kornat, Marek (1971– ) (Instytut Historii PAN, 2024)
A critical issue that arose during the international crisis of 1934–38 was a potential passage of Red Army troops through Polish territory in case the USSR entered war as an ally of France (or France and Great Britain) against Germany. It became especially relevant in the summer of 1938 with the emergence of the Sudeten Crisis. The present article is the first historiographic study to discuss this issue as a separate subject.
p. 5-27
Summary in English and Polish
Keywords: Poland; USSR; France; international crisis 1938